Influências greco-romanas na Hispânia: colonização, arquitetura e urbanismo de Emerita Augusta (séculos I a.C. ao II d.C.) - De Leão, Natália Munaro (2015)
This study analyzes the trajectory of expansion of Western Greco-Roman colonization along the Mediterranean, until reaching Iberian Peninsula. Therefore, it verified political-strategic importance and wealth of resources Hispania territory used to offer, attracting Mediterranean colonizers who founded several colonial towns in order to settle at the peninsular territory. Through the phenomenon of colonization, trades and inter-ethnic contacts, Greco-Roman colonial towns have achieved great success and led Iberian Peninsula to a long process of cultural influences by both Hellenism and Romanization, culminating, thus, in Greek-Roman culture spreading in Hispania. Ancient colonial towns have registered Greco-Roman influences that has remained expressed via urbanism and architecture, legated to posterity mainly by its ruins of monuments and buildings found in situ. Process of Romanization was highlighted in this study based on analysis of archaeological, architectural and urban vestiges evidence of the capital of Province of Hispana Ulterior of Lusitania the Roman colonial town of Emerita Augusta during the High Roman Empire period. Characteristics that used to comprise a Roman colonial town can show how magnificent and influent this provincial town was then, besides revealing the importance of that culture in antiquity and their influence to the present.